Complaints as Opportunity for Change in Encounters between Youths and Police Officers - Tove Pettersson (Social Inclusion, 2014)
The presence of distrust in the police and how they perform their work among ethnic minority youths in socially underprivileged areas is well established. Experiences of, or beliefs about, unfair treatment from the police can be viewed both as an indicator and a consequence of exclusion. It is well-known that negative experiences of the police are more significant for trust in the police and their legitimacy than positive ones, with some even suggesting that positive experiences do not matter at all. However, from a procedural justice perspective it has been suggested that some positive experience do matter, particularly if the police are considered to perform their work in line with procedural fairness. On the basis of a participant observation study, this article discusses situations in which youths express complaints about the police in different ways. In response to such situations, the police can act in both exclusionary and inclusive ways. It is argued that youths’ complaints can be used as an opportunity for change if the police treat the youths concerned with fairness and in inclusive rather than exclusionary ways.